KNITTING TOGETHER THE URBAN FABRIC: Visions of the Past & Future on Shelburne Road - Pepin, Ethan (Tufts University Tisch Library, 2025)
Thesis (M.A.)--Tufts University, 2025.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Rebecca Shakespeare.; Committee: Christine Cousineau.; Keyword: Urban planning